Sulfonated polymeric zinc oxide-based nanocatalysts for methyl ester production - Soltani, Soroush (2016)
The increasing production growth and economic developments have increased not only the consumption of energy but also increased the level of pollutants. It is assumed that fossil fuels would be eliminated in years to come, which alerted an urgent need to switch to the renewable energy sources (RESs). In this research work, high free fatty acid feedstock, palm fatty acid distillate (PFAD), has been explored as non-edible feedstock for biodiesel production using efficient mesoporous zinc oxide (ZnO) based nanocatalysts. The main purpose was to develop the mesoporous ZnO based catalysts to enhance the conversion rate of biodiesel production for PFAD. An efficient mesoporous ZnO based nanocatalysts were hydrothermally fabricated, using the polyethylen glycol (PEG) as a surfactant and D-glucose as a template. The effects of different zinc nitrate concentration and different calcination temperature were determined on the structural and textural properties. Surface functionalization is a beneficial approach which improves the adsorption capacity and surface activity of the parent materials. One route is the doping of the metal nanoparticles as support into pre-fabricated materials. In this project, ZnO has been functionalized with Al and Cu in order to improve its textural properties. Zinc aluminate (ZnAl2O4) and zinc-cupper (CuO-ZnO) mixed metal oxides possess superior advantages such as high surface area and high thermal stability. Post-sulfonation treatment is another approach which was done in order to modify the hydrophobicity via attaching of ─SO3H groups on the active sites. Furthermore, the effect of sulfonation conditions on catalytic activity was also examined. It was observed that sulfonation under severe conditions led to the reduction of the textural properties. The palm fatty acid distillate (PFAD) was chosen as feedstock for biodiesel production, containing high FFA (around 80-90%). In order to improve the esterification process for PFAD production, a comparison study was also carried out between two efficient autoclave and microwave heating systems over synthesized mesoporous ZnO based nanocatalysts. The influences of esterification reaction conditions (methanol to oil molar ratio, catalyst concentration, reaction temperature and reaction time) towards the catalytic performance of the synthesized nanocatalysts were also investigated to optimize the higher biodiesel yield. It was found that the functionalized mesoporous ZnO based SO3H-ZnO, SO3H-ZnAl2O4, SO3H-CuO-ZnO nanocatalysts had high catalytic activity for esterifying PFAD, giving FAME yield of 91.20%, 94.65%, and 95.76%, respectively. The recyclability of the synthesized catalysts was further evaluated. According to the recyclability results, the mesoporous ZnO based nanocatalysts were able to remain active for at least eight consecutive runs without using further treatment. Furthermore, the physico-chemical characteristics of the biodiesel produced from PFAD were tested with compliance to EN14214 and ASTM D6751 standards. The key fuel properties of the produced PFAD biodiesel were all within range of the mentioned standards. As a conclusion, from all the results, it was found that the synthesized sulfonated mesoporous ZnO based nanocatalysts had great potential to catalyze high FFA feedstock (PFAD) for biodiesel production with high recyclability. The excellent activity and recyclability of the catalyst may be assigned to the combination of unique textural properties and polymeric attachment of the ─SO3H functional group to the surface of the catalyst. The esterification reaction under solvo-thermal methods resulted in high biodiesel yield in shorter reaction rate, especially using microwave heating system.